Combination Of Integrated Marketing Communication and Brand Equity Baitul Maal Wat Tamwil in Maintaining Customer Loyalty - Farida, Nasyiatul; Najwa Kirana, Galuh; Jalaluddin, Bilal; Arifin, Moh; Majid Toyyibin, Abdul (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2024)
This research aims to find out how the combination of integrated marketing communication and brand equity has a technical role for BMT in maintaining and increasing the loyalty of BMT UGT Nusantara Arosbaya members. The research method used is qualitative research with a field research approach, namely explaining, describing and describing problems that are closely related to this research. The research results show that marketing communication and brand equity to maintain member loyalty is by using integrated marketing communication, which combines a marketing concept from many promotional elements to the public in a structured and integrative manner, which is called the marketing communication mix.